The epigenetic pioneer EGR2 initiates DNA demethylation in differentiating monocytes at both stable and transient binding sites - Karina Mendes (Nature Portfolio, 2021)
DNA methylation turnover is an essential epigenetic process during development. Here, the authors look at the changes in DNA methylation during the differentiation of post-mitotic human monocytes (MO), and find that EGR2 interacts with TET2 and is required for DNA demethylation at its binding sites; revealing EGR2 as an epigenetic pioneer factor in human MO.